The Role of Emotional Intelligence in Leadership Effectiveness: A Cross-Industry Analysis - Dadang Irawan; Seger Santoso; Mia Christy Patricia (LPPM STIE Kasih Bangsa, 2024)
This study investigates the impact of emotional intelligence (EI) on leadership effectiveness across diverse industries. Utilizing a mixed-methods approach, data was collected through surveys and interviews from leaders in various sectors. Quantitative analysis revealed a significant positive correlation between leaders' EI levels and their effectiveness in guiding teams and achieving organizational goals. Qualitative insights further elucidated how EI competencies such as self-awareness, social awareness, self-regulation, and relationship management influence leadership behaviors and outcomes. Findings suggest that leaders with higher EI tend to exhibit better interpersonal skills, conflict resolution abilities, and adaptability, resulting in enhanced team performance and organizational success. The study underscores the importance of EI development programs for leaders across industries to improve leadership effectiveness and foster a positive work environment conducive to growth and innovation.